Cash incentives to mothers or to community health workers - what contributes better to the health of the mother and the newborn? Evidence from India - Susmita Baulia (Aboa Centre for Economics (ACE), 2020)
This paper investigates the role of demand-side incentives to mothers and supply-side incentives to community health workers (ASHAs) in improving maternal and child healthcare. These conditional cash benefits were part of a nationwide health intervention Janani Suraksha Yojana, introduced in India in 2005. By its unique dual focus on demand and supply, the programme entitled socio-economically backward mothers with cash assistance if they chose to give birth at public health institutions, and simultaneously employed ASHAs to act as an immediate link between a pregnant woman and the public health delivery system. By using variations across eligibility of mothers, and the differential implementation of ASHAs across low-focus and high-focus states, I find causal evidence that eligible mothers who received both cash benefits and ASHA's counselling outperformed the eligible mothers receiving only cash benefits, in outcomes such as institutional births and breastfeeding practices. To elucidate, a mother with both cash benefits and ASHA's counselling experienced a 7.1 percentage points increase in institutional birth rate than her ineligible counterpart; whereas, the corresponding increase for a mother only eligible for cash benefits was 2.9 percentage points. Similar impact is found in the case of antenatal care check-ups of the expecting mother and BCG vaccination of the newborn.
Keywords: I10; I38; 330; Conditional Cash Transfer; maternal health; child health; difference-in-difference; coarsened exact matching